Method and composition for making mesoporous carbon coated monolith - Choong, Thomas Shean Yaw; Hosseini, Soraya; Malekbala, Mohamad Rasool; Abdullah, Luqman Chuah (2012)

(untitled)
A method for fabricating a mesoporous carbon coated material includes the steps of mixing a precursor composition to form a polymer solution, coating a substrate in the polymer solution and heating the polymer solution and the substrate at a carbonizing temperature for sufficient time under nitrogen gas to form a mesoporous carbon coated monolith. The precursor composition includes a carbon precursor, a template, a cross-linking agent, a solvent and a catalyst. The mesoporous carbon coated monolith is characterized by a large pore volume for adsorbing multiple molecules.